2005
DOI: 10.1007/s11172-005-0319-z
|View full text |Cite
|
Sign up to set email alerts
|

Annelation of drotaverine by p-quinones to form hydroxyindolo- and hydroxybenzindoloisoquinoline derivatives

Abstract: 1 (3,4 Diethoxybenzyl) 6,7 diethoxy 3,4 dihydroisoquinoline (drotaverine, 1a) reacts with p benzoquinone (2) and p naphthoquinone (3) in nitromethane or during fusion to give 5 (3,4 diethoxyphenyl) 7,8 diethoxy 3 hydroxy 5a,10,11,12 tetrahydroindolo[2,1 a]iso quinoline (4) and 7 (3,4 diethoxyphenyl) 9,10 diethoxy 5 hydroxy 7a,12,13,14 tetra hydrobenz[g]indolo[2,1 a]isoquinoline (5), respectively. Compounds 4 and 5 are smoothly alkylated at the oxygen atom in the presence of bases. The structure of one alkylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Thus, NMR experimental data demonstrate the absence of intramolecular tautomerism in drotaverine hydrochloride. The obtained conclusion corresponds to the data in the scientific literature on the mechanism of tautomerism in drotaverine hydrochloride . According to the authors’ conclusion, the intramolecular isomerization of the azomethine (I) and enamine (II) structures in drotaverine hydrochloride is considered unlikely due to unfavorable steric conditions for 1,3‐proton transfer that requires overcoming a large energy barrier .…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Thus, NMR experimental data demonstrate the absence of intramolecular tautomerism in drotaverine hydrochloride. The obtained conclusion corresponds to the data in the scientific literature on the mechanism of tautomerism in drotaverine hydrochloride . According to the authors’ conclusion, the intramolecular isomerization of the azomethine (I) and enamine (II) structures in drotaverine hydrochloride is considered unlikely due to unfavorable steric conditions for 1,3‐proton transfer that requires overcoming a large energy barrier .…”
Section: Resultssupporting
confidence: 86%
“…It should be noted that NMR spectroscopy and X‐ray diffraction analysis (XRD) are direct methods that establish the structure of organic compounds without using standards and are specific to double bond position isomers. The results of the study of the structure of the compound II using these methods can be found in literature . There are no published NMR or XRD data for the compound I.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation